Assessing the Topsoil Contamination of Cesium-137 Environmental Fallout in Konya, Turkey: Spatial Distribution and Analysis - Gunay, Osman; Ozden, Selin; Pehlivanoglu, Serpil Akozcan (SPRINGER INT PUBL AG, 2023)
Although more than 30 years have passed since the Chernobyl accident, artificial radionuclides are still present in the soil. Especially, 137Cs is harmful to human health and contamination due to 137Cs is high. The topsoil samples were collected from various locations in Konya, Turkey. 137Cs activity concentrations were measured using coaxial high-purity germanium gamma-ray spectrometry. 137Cs activity concentrations in the surface soil samples ranged from 0.74 +/- 0.08 to 12.88 +/- 0.86 Bq kg-1 dry weight (d.w.). The absorbed dose rate and the annual effective dose rates for outdoor and indoor air were estimated. The mean values of the absorbed dose rate and the outdoor and the indoor annual effective dose rates were found as 0.09 nGy h-1, 0.11 mu Sv y-1, and 0.43 mu Sv y-1, respectively. The obtained activity concentrations and annual effective dose rates were compared with other studies. The spatial distributions of 137Cs activity concentrations and dose rates were plotted using the Surfer Program. The Kriging interpolation method is used to obtain the distribution maps of 137Cs radionuclide. Frequency distribution and quantile-quantile plots were carried out.
Keywords: Chernobyl accident; Cesium-137; Radioactivity; Soil; ECOLOGICAL HALF-LIFE; EASTERN BLACK-SEA; NATURAL RADIOACTIVITY; RADIOLOGICAL HAZARDS; CS-137 CONTAMINATION; CHERNOBYL; RADIOCESIUM; SAMPLES; REGION; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources